2020
DOI: 10.5603/ocp.2020.0004
|View full text |Cite
|
Sign up to set email alerts
|

Summary of immunotherapy efficacy ordered in accordance with drug reimbursement program in melanoma patients

Abstract: Nivolumab and pembrolizumab are monoclonal antibodies of the IgG4 class, which target the cell death receptor (PD-1) found on T cells. The binding of the anti-PD-1 drug to the receptor therefore prevents the inhibition of these T cells and increases the immune response against melanoma cells. Pembrolizumab and nivolumab monotherapy has similar efficacy, including PFS and OS. Nivolumab and pembrolizumab immunotherapy are effective regardless of the BRAF mutation status. Currently, the choice between nivolumab a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Safety of nivolumab in patients with advanced melanoma routinely treated was shown to be consistent with previously published data from clinical trials [21,22], but in every day practice higher number of rheumatoid irAEs is reported than in the trials. This may be due to preexisting conditions and higher age of patients treated outside randomized clinical trials [22,23]. As expected the toxicity of nivolumab-ipilimumab combination, also in real-world data, is higher and any grade irAEs are experienced by 88% of patients, while grade 3 or 4 by more than 50% [24].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Safety of nivolumab in patients with advanced melanoma routinely treated was shown to be consistent with previously published data from clinical trials [21,22], but in every day practice higher number of rheumatoid irAEs is reported than in the trials. This may be due to preexisting conditions and higher age of patients treated outside randomized clinical trials [22,23]. As expected the toxicity of nivolumab-ipilimumab combination, also in real-world data, is higher and any grade irAEs are experienced by 88% of patients, while grade 3 or 4 by more than 50% [24].…”
Section: Introductionmentioning
confidence: 68%
“…At the same time hydroxychloroquine activity block the late stages of autophagic proteolysis and does not alter the antitumor T cell response [81]. Multidisciplinary (MDT), treatment with close monitoring is absolutely required in these cases and rheumatologist or dermatologist should be enrolled into such MDT [23]. It should be remembered that autoimmune disease also differ by background that is GBS is classically B cell-mediated disease, while rheumatoid arthritis or Sjogren's syndrome result from chronic inflammation with PD-1 positive T cell infiltrates in the tissues [82].…”
Section: Safety Of Nivolumab In Challenging Subgroups Of Patientsmentioning
confidence: 99%